DEVELOPMENT OF IDENTITY MANAGEMENT SYSTEM WITH BLOCKCHAIN TECHNOLOGY USING HYPERLEDGER FABRIC - Muhammad Asnadi, Ihsan
Identity Management System is expected to manage identity since the creation, distribution, until revocation. Identity is a set of attributes that represents an individual both in the real life and the internet. This thesis will elaborate challenges that are faced by Identity Management System—single point of failure, asset provenance, trust, key management, identity lifecycle management, and identity roaming—and also proposes system design to solve those challenges with blockchain technology. Blockchain is a part of distributed system. Blockchain consists of peers that are coordinated with each other to store transactions. Every transactions will be visible for each peer. Transactions will be stored with append-only operation—this means that every changeset towards the asset can be traced back and there is no way to change the asset discreetly without known by other peers. This system was developed using Hyperledger Fabric. This system consists of blockchain network configuration and chaincode to enforce business logic. Blockchain network can solve single point of failure because blockchain network is a distributed system. Asset provenance can be solved using blockchain because blockchain uses append-only operation—this ensures that every changeset will be logged. Trust is partially solved because Hyperledger Fabric as a permissioned blockchain still needs trust through the usage of Public Key Infrastructure. Key management can only be achieved through using external tools such as Vault by HashiCorp. Identity lifecycle management can be achieved through the development of chaincode on top of blockchain network. Identity roaming scheme is achieved as the consequences of using blockchain— or more accurately, distributed ledger—as the architecture. The next step after implementing the system is testing the system. Based on the result of testing, it can be inferred that blockchain technology cannot fully solve all the challenges that are faced by Identity Management System. This system can implement identity roaming easily through the usage of channel, but on the other hand, this system still depends on trust through the usage of Public Key Infrastructure. Thus, there is a need to do further research to incorporate other methodologies to solve all the challenges.